2006
DOI: 10.1523/jneurosci.3420-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Directional Signals in the Prefrontal Cortex and in Area MT during a Working Memory for Visual Motion Task

Abstract: Neurons in the middle temporal visual area (MT) have been implicated in the perception of visual motion, whereas prefrontal cortex (PFC) neurons have been linked to temporary storage of sensory signals, attentional and executive control of behavior. Using a task that placed demands on both sets of neurons, we investigated their contribution to working memory for visual motion. Monkeys compared the direction of two moving random-dot stimuli, sample and test, separated by a brief memory delay. Neurons in both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
199
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(239 citation statements)
references
References 75 publications
36
199
4
Order By: Relevance
“…Both in Experiment 1 and 2 controls for the confounding factor motion coherence (Figs 6b and 9b) made it improbable that the late ERP dissociation represented more frontal contributions to working memory for visual motion observed in previous moving random-dot experiments 27 . Rather one may well ask whether electrophysiological or imaging findings are-at least for comparable discrimination tasks-confounded by correlates of subjective confidence in the perceptual decision.…”
Section: Discussionmentioning
confidence: 86%
“…Both in Experiment 1 and 2 controls for the confounding factor motion coherence (Figs 6b and 9b) made it improbable that the late ERP dissociation represented more frontal contributions to working memory for visual motion observed in previous moving random-dot experiments 27 . Rather one may well ask whether electrophysiological or imaging findings are-at least for comparable discrimination tasks-confounded by correlates of subjective confidence in the perceptual decision.…”
Section: Discussionmentioning
confidence: 86%
“…B 372: 20160111 execute cognitive functions is related to the interindividual variability in the perception of visual motion. As described above, the neurons in the PFC (BA 46) exhibit motion sensitivity [38,39] and function to allocate attention to a visual target in the object-centred coordinate [36,37], while a higherorder, attention-driven motion mechanism functioning on the spatiotopic coordinate would be responsible for the induction of motion assimilation [12,21,22]. Additionally, a relationship between Glx concentrations and the function of attention has been found in adults with attention-deficit hyperactivity disorder (ADHD) [40] or autism spectrum disorders (ASD) [41].…”
Section: Discussionmentioning
confidence: 94%
“…Thus, we examined whether neurotransmitter concentrations in the dorsolateral PFC (Brodmann area BA 46) are correlated with individual differences in motion perception. We targeted this area because neurons inside are involved in attention allocation to a target in an object-centred coordinate [35,36], they are connected with the visual areas including the MT [37], and they encode both visual motion direction and speed information [38,39]. We expected that the Glx is important because its concentration has been shown to be related to the attentional status [40,41], which could affect perception of motion assimilation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent recordings from the PFC during motion discrimination tasks revealed direction-selective (DS) responses that depended on behavioral context, shedding light on the nature of the top-down signals PFC is likely to provide (3,4). These and other studies (e.g., ref.…”
mentioning
confidence: 79%
“…Stimuli, behavioral tasks, and physiological recordings have been described in previous studies (3,4). Specific methodological details relevant to the current study can be found in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%